Recurrent chest pain and dyspnoea in a patient with pulmonary arterial hypertension. Issue 4 (4th July 2019) - Van Tittelboom, Nathalie; Devos, Dan; Thierry, Bové; De Pauw, Michel; Vandecasteele, Els
ABSTRACT: Background : Pulmonary arterial hypertension (PAH) is a devastating, life-threatening disease with poor prognosis when left untreated. The long-term prognosis is definitely influenced by the natural progression of PAH but late disease-specific complications may also contribute. Case summary : We present a patient with a long-standing idiopathic PAH in whom progressive dilatation of pulmonary trunk and pulmonary arteries leads to compression of the left main coronary artery and the left atrium with hemodynamic compromise. Conclusion : With the current treatment options, survival in PAH has improved. Guidelines focus on more aggressive treatment with initial combination therapy and earlier referral for transplantation.